2022
DOI: 10.1684/epd.2022.1479
|View full text |Cite
|
Sign up to set email alerts
|

An epilepsy curriculum for primary health care providers: a report from the Education Council of the International League Against Epilepsy

Abstract: Objective. Primary health care providers are directly responsible for the care of people with epilepsy. However, their education about epilepsy might be inadequate or lacking. Our objective was to develop an evidence-based and consensus-driven educational curriculum for the management of epilepsy within the primary healthcare setting. Methods. The International League Against Epilepsy (ILAE) Education Council commissioned a task force of international experts, who met virtually at monthly intervals in 2020/202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…(5) ability to manage epilepsy emergencies including status epilepticus; and (6) ability to recognize and provide primary care for psychiatric and somatic comorbidities and suggest to facilitate future primary health care epilepsy education packages. 22 Comparing the curriculum domains provided by ILAE, it can be seen that training needs domains including the family medicine/ general practitioner approach in the present study. The curriculum provided by ILAE overlaps in many ways with the training needs identified by the present study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…(5) ability to manage epilepsy emergencies including status epilepticus; and (6) ability to recognize and provide primary care for psychiatric and somatic comorbidities and suggest to facilitate future primary health care epilepsy education packages. 22 Comparing the curriculum domains provided by ILAE, it can be seen that training needs domains including the family medicine/ general practitioner approach in the present study. The curriculum provided by ILAE overlaps in many ways with the training needs identified by the present study.…”
Section: Discussionmentioning
confidence: 68%
“…Although a question was asked about the type of education received in the study and its content, most participants did not answer it, so it cannot be commented on whether this finding is related only to education or another confounding factor. In the report, the current version of the ILAE primary health care epilepsy educational curriculum's six domains were provided: (1) ability to diagnose epilepsy and its broad subtypes; (2) ability to provide counseling to people with epilepsy over a range of issues; (3) ability to introduce treatment and follow‐up to people with epilepsy; (4) competency to refer people to higher centers of care appropriately; (5) ability to manage epilepsy emergencies including status epilepticus; and (6) ability to recognize and provide primary care for psychiatric and somatic comorbidities and suggest to facilitate future primary health care epilepsy education packages 22 . Comparing the curriculum domains provided by ILAE, it can be seen that training needs domains including the family medicine/general practitioner approach in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An international survey found that a third of epilepsy care providers, including those from LMICs, diagnose psychiatric disorders only when individuals spontaneously report psychiatric symptoms [45]. Another international survey by the International League Against Epilepsy clearly emphasized the low priority accorded to psychiatric comorbidities of epilepsy by specialists and primary care providers worldwide [46]. More recently, however, and in step with screening recommendations for psychiatric comorbidities on an annual basis, awareness about psychiatric disorders has increased among epilepsy specialists [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the knowledge and awareness of primary health care workers through the training curricula developed by the International League Against Epilepsy Education Council will improve the knowledge and attitudes of society. 37 This study has some limitations. First, the data were obtained only from people who applied to the education family health centers in Samsun.…”
Section: 5mentioning
confidence: 91%